Re-Examining the Anatomy of Islamic Psychotherapy and Counselling: Envisioned and Enacted Practices - Rassool, Goolam Hussein (Islamic Guidance and Counseling Journal, 2021)
Islam is a major world religion and is considered one of the Abrahamic, monotheistic faiths, focusing on monotheistic beliefs. The population of Muslims is estimated to be over one billion people and it is a heterogeneous rather than homogeneous community. Muslim communities are made of different races, ethnic groups’ nationalities, and cultures across the globe and united by their common Islamic faith. There has been an exponential growth of Muslim communities in most countries of the West and Southern hemispheres. This growth has resulted in an increased prevalence of psychosocial and mental health problems leading to a demand for psychotherapeutic and mental health services. The increased mental health problems among the Muslim communities have brought new challenges to therapists to provide a non-Eurocentric therapy approach based on the worldview of their Muslim clients. It is argued that mainstream psychology has lost its ‘soul’ and is largely devoid of the psycho-spiritual concerns of its clients. The therapeutic interventions of mainstream therapies, based upon a mono-cultural perspective, are failing to meet the holistic needs of Muslims. Based on the increasing recognition of the need to provide holistic therapy, a new paradigm shift is needed in the development of Islamic psychotherapy and counselling.